Perspektif Gender Pada Tari Lengger Banyumas - Rahma, Julia Nur Rahma (Program Studi Pendidikan Tari FBS UNJ, 2024)
Describe and analyze the gender perspective on the Lengger Banyumasan dance. The method used is qualitative research, with data collection techniques of observation, interviews and documentation. Data were analyzed by triangulation. The results of the study indicate that this dance originates from Banyumas, this dance is presented for entertainment